Hypersonic boundary layer instability measurements at Mach 7 and flight total enthalpy - Wylie, S; McGilvray, M; Raghunath, S; Mee, D (2019)
This paper presents boundary layer instability measurements obtained in The University of Queensland’s T4 Stalker Tunnel at Mach 7. The model geometry is a 7◦ half angle cone with a nose bluntness of 1.55 mm radius, pitched at an angle of attack of zero degrees. Results are presented at a constant enthalpy (H0 = 2.0–2.4 MJkg−1 ), a sweep of unit Reynolds numbers (Reunit,∞ = 5.0–12.0 × 106 /m), and three wallto-total temperature ratio distributions (Tw/T0 = 0.12 – 0.19). The cone nosepiece is instrumented with a DC powered heater cartridge, allowing it to reach temperatures up to 433 K at the tip. Continuous wavelet analysis and power spectral density results suggest that a disturbance may exist at a frequency of ≈ 750 kHz. The frequency and amplitude of the suspected disturbance did not appear to change for the limited Tw/T0 distributions tested. The results suggest that only the early stage of growth was detected, with a maximum amplitude of 8.1% reached.